(untitled) (One Health & Risk Management, 2023)
Introduction. Abortion causes problems in reproductive health, relationships in a couple, psychological and social consequences. A woman’s decision to have an abortion depends on many factors, whereas in low-income countries, abortion is viewed as a method of family planning. Material and methods. A descriptive, quantitative and qualitative sample study was conducted in the Republic of Moldova from December 2021 to February 2022 to identify and evaluate the factors influencing a woman’s decision-making to terminate a pregnancy, as well as to develop recommendations for reducing the number of abortions on demand. The quantitative assessment included a survey carried out on a sample of 399 women who underwent abortions on demand. The qualitative study involved three focus group meetings, where the obstetrician-gynecologists shared their ideas upon the factors determining a woman’s decision to terminate a pregnancy. Results. Analyzing the data obtained, the present research identified the following factors that determined the decision-making of women to terminate a pregnancy: (i) lack of support and disturbed psycho-emotional state in women; (ii) social and economic problems, particularly, poverty; (iii) study/career-related conditions; (iv) age; e) difficult relationship with the partner, particularly, domestic violence; (v) fear of COVID-19 infection. Conclusions. Women’s reasons for seeking abortions are complex, traced out by circumstantial and systemic realities.